Comparison of anterior section parameters using anterior segment optical coherence tomography and ultrasound biomicroscopy in myopic patients after ICL implantation - Jing Zhang; Hui-Hui Luo; Jing Zhuang; Ke-Ming Yu (International Journal of Ophthalmology, 2016)
AIM: To compare the agreement of anterior chamber depth (ACD) and central vault measurements obtained by anterior segment optical coherence tomography (AS-OCT) and ultrasound biomicroscopy (UBM) of post surgical high myopic eyes with posterior chamber phakic intraocular lens (Visian ICL; STAAR Surgical) implantation. METHODS: Fifty-two phakic eyes of 28 high myopic patients who underwent implantable Collamer lens (ICL) surgery for the correction of high myopia were studied. The postoperative ACD, the distance between the corneal endothelium and the anterior surface of ICL (cornea-ICL) and the central vault were measured with the AS-OCT system and the UBM system. Intraclass correlation coefficient (ICC) and the Bland-Altman plot were used to evaluate the repeatability and agreement of two devices. RESULTS: The mean ACD, cornea-ICL and central vault in the 52 phakic eyes after ICL surgery was 3.19±0.28 mm, 2.47±0.28 mm, 0.50±0.19 mm by AS-OCT and 3.13±0.25 mm, 2.49±0.25 mm, 0.44±0.19 mm by UBM, respectively. Pairwise comparison of ACD and central vault measurements showed significant differences between AS-OCT and UBM (P<0.05). However, no statistically significant difference was found between these imaging techniques in cornea-ICL (P>0.05). The Pearson correlation coefficient (r) between AS-OCT and UBM measurements for ACD, cornea-ICL and vault was 0.88, 0.80 and 0.89, respectively (P<0.001). The ICC was 0.89-0.94 for the measurements of AS-OCT and UBM. Bland-Altman analysis showed the 95% limits of agreement of ACD, cornea-ICL, central vault measurements between these two devices were -0.20 to 0.32 mm, -0.36 to 0.32 mm and -0.12 to 0.24 mm, respectively. CONCLUSION: Central ACD and vault measurements using AS-OCT demonstrated a slight significantly higher value than using UBM in phakic eyes after ICL surgery. These two devices should not be used interchangeably for measurements of central ACD and vault in patients after phakic intraocular lens implantation.